Assessment of hemagglutinin-inhibition activity following influenza vaccination during the 2022–2023, 2023–2024, and 2024–2025 seasons - Engin Berber; Hannah B. Hanley; Brianna M. Gamez; Ted M. Ross (PLoS ONE, 2026)
Seasonal influenza vaccines are available in multiple formulations including egg-based inactivated standard-dose, cell-based inactivated, recombinant, and live-attenuated. However, vaccine effectiveness and antibody responses vary by vaccine type, recipient age, and prior influenza exposures. Both age and repeated annual vaccination can modulate immune outcomes through antigenic differences between historical and updated vaccine formulations. In this three-season (2022–2023–2024–2025) study, 1,328 participants aged 9–89 years received one of six vaccine types (Fluzone standard dose (SD) or high dose (HD), Fluad, Flucelvax, Flublok, Flumist). Collected serum samples were tested for hemagglutination inhibition (HAI) activity against vaccine strains and historical circulating strains before vaccination and day 28 post-vaccination. Seroprotection and seroconversion rates were analyzed by age group and vaccine platform. Repeated vaccination across consecutive seasons was associated with reduced HAI boosting to current vaccine strains in some participants, although vaccination broadly increased antibody titers to prior strains (back-boosting) and maintained high seroprotection rates from year to year. Participants ≥65 years had lower post-vaccination HAI titers compared to younger adults and had rapid waning of HAI titers than vaccinated younger adults, yet elderly participants with HAI titers <1:40 had higher seroconversion rates following vaccination, which may in part reflect lower baseline titers in this group allowing a ≥ 4-fold rise to meet the seroconversion definition with Fluzone HD or Fluad adjuvanted vaccines compared to younger vaccinated participants. Over the three seasons, younger adult participants vaccinated with Flublok had higher HAI titers than participants vaccinated with Fluzone SD against H1N1 and H3N2 strains. In contrast, post-vaccination HAI titers in elderly participants were comparable between Fluzone HD and Fluad recipients for each vaccine component, including influenza A and B strains. Participants vaccinated with Flumist had low or no measurable serum HAI activity. Overall, the elicitation of vaccine induced immune responses is strongly influenced by vaccine formulation, age and immune history of the participant.